2018
DOI: 10.11606/s1518-8787.2018052000153
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa de custo da asma em tratamento ambulatorial: estudo com dados de mundo real

Abstract: OBJECTIVE To estimate the cost of diagnosis and treatment of asthma.METHODS We used the perspective of society. We sequentially included for 12 months, in 2011-2012, 117 individuals over five years of age who were treated for asthma in the Pneumology and Allergy-Immunology Services of the Piquet Carneiro Polyclinic, Universidade do Estado do Rio de Janeiro. All of them were interviewed twice with a six-month interval for data collection, covering 12 months. The cost units were identified and valued according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 29 publications
0
20
0
6
Order By: Relevance
“…Asthma is one of the most common non-communicable respiratory disease, affecting about 6% of general population, that is currently more than 300 millions of people in the world1, 2; the trend of asthma prevalence seems to be at least stable, 1 if not even increasing in the last few years 2, 3. This epidemiological situation accounts for high and increasing health-related costs (direct and indirect),4, 5, 6, 7, 8, 9 particularly in those patients with suboptimal control of asthma 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is one of the most common non-communicable respiratory disease, affecting about 6% of general population, that is currently more than 300 millions of people in the world1, 2; the trend of asthma prevalence seems to be at least stable, 1 if not even increasing in the last few years 2, 3. This epidemiological situation accounts for high and increasing health-related costs (direct and indirect),4, 5, 6, 7, 8, 9 particularly in those patients with suboptimal control of asthma 10, 11…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 Another study found that a patient with severe asthmatic has an annual cost of US$1400, that is two to four times more when compared with patients with milder asthma. 21 …”
Section: Methodsmentioning
confidence: 99%
“…(15) Uncontrolled asthma generates high costs for the health care system as well as for families. (16) In cases of severe asthma, it is estimated that this corresponds to more than a quarter of the family income among users of the Brazilian Sistema Único de Saúde (SUS, Unified Health Care System), (16,17) although the cost could be reduced significantly with the adequate control of the disease. (18) However, a nationwide survey found that only 12.3% of asthma patients had well-controlled asthma.…”
Section: Epidemiology Of Asthma In Brazilmentioning
confidence: 99%